Myelin Oligodendrocyte Glycoprotein Antibody-Associated Disorders: Toward a New Spectrum of Inflammatory Demyelinating CNS Disorders? - Di Pauli, Franziska; Berger, Thomas (Frontiers in Immunology, 2018)
Inflammatory demyelinating CNS syndromes include, besides their most common entity multiple sclerosis, several different diseases of either monophasic or recurrent character – including neuromyelitis optica spectrum disorders and acute disseminated encephalomyelitis. Early diagnostic differentiation is crucial for devising individual treatment strategies. However, due to overlapping clinical and paraclinical features diagnosis at the first demyelinating event is not always possible. A multiplicity of potential biological markers that could discriminate the different diseases was studied. As the use of autoantibodies in patient management of other autoimmune diseases, is well established and evidence for the critical involvement of B cells/antibodies in disease pathogenesis in inflammatory demyelinating CNS syndromes increases, antibodies seem to be valuable diagnostic tools. Since the detection of antibodies against aquaporin-4, the understanding of immunopathogenesis and diagnostic management of neuromyelitis optica spectrum disorders has dramatically changed. However, for most inflammatory demyelinating CNS syndromes, a potential antigen target is still not known. A further extensively studied possible target structure is myelin oligodendrocyte glycoprotein, found at the outermost surface of myelin sheaths and oligodendrocyte membranes. With detection methods using cell-based assays with full-length, conformationally correct myelin oligodendrocyte glycoprotein, antibodies have been described in early studies with a subgroup of patients with acute disseminated encephalomyelitis. Recently, a humoral immune reaction against myelin oligodendrocyte glycoprotein has been found not only in monophasic diseases, but also in recurrent non-multiple sclerosis diseases, particularly in paediatric patients. This review presents the findings regarding myelin oligodendrocyte glycoprotein antibodies as potential biological markers in discriminating between these different demyelinating CNS diseases, and discusses recent developments, clinical implementations, and data on immunopathogenesis of myelin oligodendrocyte glycoprotein antibody-associated diseases.